1996
DOI: 10.1007/bf00731436
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant glycosylation of IgA from patients with IgA nephropathy

Abstract: Despite the prominent role of IgA, particularly IgA1, in the pathogenesis of IgA nephropathy (IgAN), the precise role of this molecule in the process remains unclear. Four biotin-conjugated lectins in sandwich-type enzyme-linked immunosorbent assays were devised to determine the glycosylation profiles of total IgA and its subclasses. We took advantage of differential binding properties of these lectins to sugar residues to dissect the oligosaccharide chains O-linked to the hinge and those N-linked to the Fc re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Several recent studies have shown that a portion of IgA1 molecules in sera of IgAN patients display alterations in O-linked (9)(10)(11)(12)(13)(14)(15)(16)(17), and perhaps N-linked (10), glycans. The most frequently encountered changes were restricted to Gal (9)(10)(11)(12)(13)(14)(15)(16)(17) and NeuNAc (14) in O-linked IgA1 hinge region glycans, as determined by reactivities with NeuNAc-, Gal-, and GalNAc-specific lectins and direct carbohydrate analyses. Studies of lectin reactivities of serum fractions from IgAN patients and from healthy individuals obtained by size-exclusion chromatography revealed Gal-deficient IgA1 molecules in high-molecular-mass fractions containing IgA1 and IgG (9).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that a portion of IgA1 molecules in sera of IgAN patients display alterations in O-linked (9)(10)(11)(12)(13)(14)(15)(16)(17), and perhaps N-linked (10), glycans. The most frequently encountered changes were restricted to Gal (9)(10)(11)(12)(13)(14)(15)(16)(17) and NeuNAc (14) in O-linked IgA1 hinge region glycans, as determined by reactivities with NeuNAc-, Gal-, and GalNAc-specific lectins and direct carbohydrate analyses. Studies of lectin reactivities of serum fractions from IgAN patients and from healthy individuals obtained by size-exclusion chromatography revealed Gal-deficient IgA1 molecules in high-molecular-mass fractions containing IgA1 and IgG (9).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulins with affinity for the Fc region of IgG molecules are found in rheumatoid arthritis, and the severity of the disease is associated with the extent of galactose-deficient N-glycans on Fc (8). Human IgA nephropathy has been associated with altered O-glycosylation of the IgA1 hinge region and Ig deposition in the kidney (9,10). Another possible role for aberrant glycan production in autoimmune disease includes Tn syndrome, in which reduced transcription of the core 1 O-glycan ␤1-3 GalT enzyme occurs among hematopoietic compartments.…”
mentioning
confidence: 99%
“…Although many studies have focused on the aberrant O-glycosylation of IgA in human IgAN, there are several reports suggesting that the N-glycosylation on serum IgA from IgAN patients is also defective. 50,51 This study, therefore, suggests that truncation of not only the O-glycans but also the N-glycans of IgA might participate in the development of IgAN in humans and argues that the N-glycans on IgA in the sera from IgAN patients should be analyzed in further detail. An infant patient with a mutation in the ␤4GalT-I gene, designated as a CDG-IId mutation, was reported to suffer from severe psychomotor retardation and muscle weakness.…”
Section: Discussionmentioning
confidence: 91%